Government, governance, and place-based approaches: lessons from and for public policy - Bojana Klepac; Amy Mowle; Therese Riley; Melinda Craike (BMC, 2023)
Abstract Background Place-based approaches are increasingly applied to address the determinants of health, many of which are complex problems, to ultimately improve population health outcomes. Through public policy, government actions can affect the effectiveness of place-based approaches by influencing the conceptualisation, development, implementation, governance, and/or evaluation of place-based approaches. Despite the important role of public policy, there has been limited examination of public policy related to place-based approaches. We add to the limited knowledge base by analysing Australian national public policy, to explore: (1) the definitions, conceptualisations, and characteristics of place-based approaches in public policy; (2) the government's perception and communication of its role in place-based approaches; and (3) the extent to which government policy reflects the necessary conditions for successful place-based governance developed by Marsh and colleagues, namely localised context, embedded learning, and reciprocal accountability. Methods This research was underpinned by the Theory of Systems Change and methodologically informed by the READ approach to document analysis. Ritchie and Spencer's framework method was utilised to analyse the data. Results We identified and reviewed 67 policy documents. In terms of conceptualisation, common characteristics of place-based approaches related to collaboration, including community in decision-making, responsiveness to community needs, and suitability of place-based approaches to address complex problems and socio-economic determinants of health. Three roles of government were identified: funder, partner, and creator of a supportive policy environment. From the three criteria for successful place-based governance, localised context was the most dominant across the documents and reciprocal accountability the least. Conclusions Based on our findings, we drew key implications for public policy and research. There was a disproportionate emphasis on the bottom-up approach across the documents, which presents the risk of diminishing government interest in place-based approaches, potentially burdening communities experiencing disadvantage beyond their capacities. Governments engaged in place-based approaches should work towards a more balanced hybrid approach to place-based approaches that maintain the central functions of government while allowing for successful place-based governance. This could be achieved by promoting consistency in conceptualisations of 'place-based', employing an active role in trust building, advancing the creation of a supportive policy environment, and embedding 'learning' across place-based approaches.